2013
DOI: 10.1194/jlr.r039479
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of signal transduction by HDL

Abstract: which HDL serves to shuttle cholesterol from peripheral tissues or cells to the liver. This review highlights recent advances in our knowledge of HDL-initiated processes mediated by changes in intracellular signaling in numerous cell types of relevance to both cardiovascular and metabolic conditions, which represent actions of the lipoprotein beyond its classical role in global cholesterol homeostasis. The evidence that HDL infl uences cardiovascular and metabolic health and disease will fi rst be briefl y sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 120 publications
(135 reference statements)
0
72
1
Order By: Relevance
“…2 ). Signaling via SR-BI by HDL is primarily mediated by apoA1, and in this on NO production following SR-BI mediated eNOS activation ( 17,53 ). In contrast to these studies, we found that knockdown of SR-BI and cotreatment with blocking 6.…”
Section: Hdl Effects On Transcription In the Presence And Absence Of contrasting
confidence: 92%
See 2 more Smart Citations
“…2 ). Signaling via SR-BI by HDL is primarily mediated by apoA1, and in this on NO production following SR-BI mediated eNOS activation ( 17,53 ). In contrast to these studies, we found that knockdown of SR-BI and cotreatment with blocking 6.…”
Section: Hdl Effects On Transcription In the Presence And Absence Of contrasting
confidence: 92%
“…In addition to its role in cholesterol transport, HDL possesses anti-infl ammatory, antioxidant, and antithrombotic properties (17)(18)(19). These include directly inhibiting the oxidation of LDL, sequestering by-products of lipid oxidation, and promoting eNOS stability and accumulation in the vessel wall ( 17,18,(20)(21)(22).…”
Section: Lipid Extraction and Quantifi Cation By Hplc-msmentioning
confidence: 99%
See 1 more Smart Citation
“…rHDL preparations also were formulated to contain sphingosine-1-phosphate (rHDL + S1P) at a starting molar ratio of biological responses, including inhibition of lipid oxidation, impairment of leukocyte adhesion and monocyte activation, increased nitric oxide production, prostacyclin synthesis and flow-induced vasodilation, and the prevention of endothelial cell damage and death (5)(6)(7)(8). Studies have also shown that HDL can inhibit synthesis of matrix metalloproteinases, promote smooth muscle cell proliferation, and inhibit activation of platelets and the coagulation cascade (9).…”
Section: Synthesis Of Recombinant Hdl and Recombinant Hdl Containing S1pmentioning
confidence: 99%
“…HDL apolipoprotein-mediated cholesterol removal pathway involves many cellular proteins, including cell surface binding proteins/receptors (3,4), intracellular signal transduction (3,5), vesicle transport (6,7) and exocytotic components (6,8).…”
Section: Introductionmentioning
confidence: 99%